Vida e morte ( e vida) da culpabilidade penal: contribuição à teoria do delito para um Estado Democrático de Direito - Fernando Nogueira Martins Junior (2012)
The dissertation is about the culpability crisis, important issue in contemporary Criminal Law, under a transdisciplinary approach. After a historical presentation of the concept of criminal culpabillity, it is exposed the state of the art of the discussions on the crisis of such culpability in criminal dogmatics. Subsequently, it is brought the philosophical, neurocientifical and criminological contributions to the question. After, it is made a defense of the criminal dogmatics as a insurance of the citizen before the punitive power, passing then to the presentation on how the criminal functionalisms of Claus Roxin and Eugenio Raul Zaffaroni perceived more deeply the problem and proposed interesting points to deal with such crisis. On the final considerations, it is made the vehement suggestion towards the urgent adoption, by the operators of the brazilian criminal system, of the institutes of both criminalfunctionalisms aforementioned.